The lord of the rings - Tolkien, J. R. R. (John Ronald Reuel), 1892-1973; Tolkien, J. R. R. (John Ronald Reuel), 1892-1973; Tolkien, J. R. R. (John Ronald Reuel), 1892-1973; Tolkien, J. R. R. (John Ronald Reuel), 1892-1973 (London : HarperCollins Publishers, 2011)
Building on the story begun in The Hobbit, this is the second part of Tolkien's epic masterpiece, The Lord of the Rings, featuring a striking black cover based on Tolkien's own design, the definitive text, and a detailed map of Middle-earth.
-- volume 1. The fellowship of the ring. -- volume 2. The two towers. -- volume 3. The return of the king
Keywords: Baggins, Frodo (Fictitious character) -- Fiction; Middle Earth (Imaginary place) -- Fiction; Fantasy fiction, English; Gandolf (Fictitious character) -- Fiction; Galadriel (Fictitious character) -- Fiction; Elrond (Fictitious character) -- Fiction